Crystal Structure of Dimethylformamide-tetraphenylporphyrinato-zinc(II) - Gao, Wei; Shi, Bo; Wu, Xue-Fen (Asian Journal of Chemistry, 2013)
The title compound dimethylformamide-tetraphenylporphyrinato-zinc(II) was prepared by slow evaporation from its DMF solution. Its structure was determined by single crystal X-ray diffraction analysis. The crystals are monoclinic, space group P21/c with a = 13.913(3), b = 9.3426, c = 29.539(6) Å, a = 90.00, b = 101.99(3), g = 90.00°, V = 3756.0(13) Å3, Z = 4, F(000) = 1560, Dc = 1.328 g/cm3, μ = 0.698 cm-1, the final R = 0.0803 and wR = 0.1853. A total of 26606 reflections were collected, of which 6498 were independent (Rint = 0.0991).